Influence of teaware on subjective ratings of, and taste expectations concerning, tea - Li, X; Qi, Y; Spence, C; Wan, X (Elsevier, 2019)
Two studies were conducted in order to investigate the influence of teaware on consumers’ subjective ratings of, and taste expectations concerning, one of the world’s most popular beverages, namely tea. In Study 1, 100 Chinese participants and 100 participants from the USA viewed online photographs of Chinese brand and British brand green tea presented in either Chinese or British tea sets. The participants then rated their feelings about, taste expectations concerning, and willingness-to-pay for, each cup of tea. In Study 2, 65 Chinese participants also viewed these photos with either a high or low price label for each cup of tea. The results of both studies consistently revealed that the teaware influenced Chinese participants’ bitterness and astringency ratings concerning their tea expectations; whereas no such effects were found for the USA participants. Moreover, the teaware also influenced Chinese participants’ pleasantness ratings of tea when no price information was provided, but not when price information was presented. Collectively, these findings highlight the influence of the visual appearance of the receptacle on the subjective ratings of, and taste expectations concerning, tea. These results also compare the influence of product-extrinsic and contextual cues on consumers’ taste expectations.